-4^2 + (3-5) × (-2)^3 + 3^2 - (-2)^4
Me ajudem por favorrr
Soluções para a tarefa
Respondido por
0
Olá, Leanderson. (=^.^=)/
4^2+(3-5)×(-2)^3+3^2-(-2)^4 = -7
4^2+(3-5)×(-2)^3+3^2-(-2)^4 =
4^2+(-2).8+3^2-(16) =
4^2+(-16)+9-16 =
16-16+9-16 =
25-32 = -7
Regras dos sinais:
+ com + = +
- com - = +
- com + = -
+ com - = -
Bons estudos! :-D
4^2+(3-5)×(-2)^3+3^2-(-2)^4 = -7
4^2+(3-5)×(-2)^3+3^2-(-2)^4 =
4^2+(-2).8+3^2-(16) =
4^2+(-16)+9-16 =
16-16+9-16 =
25-32 = -7
Regras dos sinais:
+ com + = +
- com - = +
- com + = -
+ com - = -
Bons estudos! :-D
leanderson15:
obg
Perguntas interessantes
Ed. Física,
11 meses atrás
Biologia,
11 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás